MEDICINE IN THE TIMURID ERA (BASED ON FRENCH SOURCES) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article discusses the events of tibia and its development in the Timurid era on the example of the work of French thinkers.In order to cover the topic of the article, the French resource was widely used.